The principle of double degree of jurisdiction in Light of Criminal Procedure Law No. 25-14 as a guarantee of a fair trial - Annane, Karima (The International tax journal, 2026)
The Algerian criminal legislator has enshrined the principle of double degree of jurisdiction since 1966 with respect to misdemeanors and contraventions, unlike felonies, until the issuance of Law No. 17-07 (now repealed), followed by Law No. 25-14, which maintained this principle. Under the latter, the Criminal Court was replaced by the Court of First Instance for Felonies, which examines acts classified as felonies at first instance, and a Criminal Court of Appeal was established as a second degree of jurisdiction. Prior to the 2017 amendment, limiting felony cases to a single degree of litigation was based on two main ideas. First, that judicial investigation was conducted on two levels: initially by the investigating judge, and subsequently by the Indictment Chamber, which was mandatorily referred every investigation concluding that sufficient evidence existed. However, despite the compulsory two-tier investigation, the existence of only one level of trial for acts considered the most serious and dangerous remained subject to significant criticism, as it undermined the principle of double degree of jurisdiction and thus constituted a clear infringement of the requirements of a fair trial.